One‐Step Sixfold Cyanation of Benzothiadiazole Acceptor Units for Air‐Stable High‐Performance n‐Type Organic Field‐Effect Transistors. Issue 11 (28th January 2021) - Kafourou, Panagiota; Park, Byoungwook; Luke, Joel; Tan, Luxi; Panidi, Julianna; Glöcklhofer, Florian; Kim, Jehan; Anthopoulos, Thomas D.; Kim, Ji‐Seon; Lee, Kwanghee; Kwon, Sooncheol; Heeney, Martin
Abstract: Reported here is a new high electron affinity acceptor end group for organic semiconductors, 2, 1, 3‐benzothiadiazole‐4, 5, 6‐tricarbonitrile (TCNBT). An n‐type organic semiconductor with an indacenodithiophene (IDT) core and TCNBT end groups was synthesized by a sixfold nucleophilic substitution with cyanide on a fluorinated precursor, itself prepared by a direct arylation approach. This one‐step chemical modification significantly impacted the molecular properties: the fluorinated precursor, TFBT IDT, a poor ambipolar semiconductor, was converted into TCNBT IDT, a good n‐type semiconductor. The electron‐deficient end group TCNBT dramatically decreased the energy of the highest occupied and lowest unoccupied molecular orbitals (HOMO/LUMO) compared to the fluorinated analogue and improved the molecular orientation when utilized in n‐type organic field‐effect transistors (OFETs). Solution‐processed OFETs based on TCNBT IDT exhibited a charge‐carrier mobility of up to μ e ≈0.15 cm 2  V −1  s −1 with excellent ambient stability for 100 hours, highlighting the benefits of the cyanated end group and the synthetic approach. Abstract : A new strongly electron‐accepting end group, 2, 1, 3‐benzothiadiazole‐4, 5, 6‐tricarbonitrile (TCNBT), has been prepared by a one‐step sixfold nucleophilic substitution reaction. Cyanation results in a significant enhancement of the electron affinity in comparison to the fluorinated analogue, and the material demonstrates promising n‐type performance in solution processed organic field‐effect transistors with excellent stability.